Temperature‐Triggered Dynamic Janus Fabrics for Smart Directional Water Transport. (12th February 2023) - Yang, Tiantian; Wang, Shi; Yang, Haoru; Gui, Haoguan; Du, Yi; Liang, Fuxin
Abstract: In this study, thermosensitive amino‐silica@PDVB/PNIPAM Janus particles (JPs) are synthesized by seed emulsion polymerization‐induced phase separation and selective modification methods. Amino‐modified silica moieties are covalently bonded to a diverse choice of substrates to achieve robust composite coatings, and a PDVB/PNIPAM abdomen forms a micro‐nano‐scale hierarchical surface. PNIPAM has a lower critical solution temperature (LCST), which allows the hydrophilic and hydrophobic properties of the coating to reverse with a change in temperature. When the fabrics are coated with the thermosensitive Janus particles, water repellency is observed above 32 °C, while hydrophilicity is revealed below 32 °C. Then, after the composite fabric is worn, the side next to the skin becomes hydrophobic due to the high temperature, and the side facing the environment is hydrophilic. Therefore, sweat can be pumped from the hydrophobic side to the hydrophilic side through the dynamic Janus fabric. The dynamic hydrophobic–hydrophilic Janus structure enables the efficient and fast evaporation of sweat. The perspiration rate of Janus fabrics is five times higher than that of commercial cotton fabrics. While the wettability of the composite coating remains reversible after 20 temperature cycles and 20 tape adhesion cycles, showing good mechanical durability. The reversible thermal sensitivity remains after repeated rubbing and ultrasonic immersion. Abstract : The Janus particles, which have a low critical solution temperature response, are connected to the fabric surface by covalent bonds, which make the hydrophilicity of Janus fabric reverse with the change of temperature. The side near the skin is hydrophobic due to heat, and the side facing the environment is hydrophilic. Sweat can be pumped through Janus fabric from the hydrophobic side to the hydrophilic side.